(untitled) (Journal of Computational Mathematics, 2022)
In this paper, we consider the Euler-Maruyama method for a class of stochastic Volterra integral equations (SVIEs). It is known that the strong convergence order of the Euler-Maruyama method is 12. However, the strong superconvergence order 1 can be obtained for a class of SVIEs if the kernels σ_i(t, t) = 0 for i=1 and 2; otherwise, the strong convergence order is 12. Moreover, the theoretical results are illustrated by some numerical examples.